Dystonic-Parkinsonian syndrome after cyanide poisoning: clinical and MRI findings. Issue 10 (October 1988) - Carella, F; Grassi, M P; Savoiardo, M; Contri, P; Rapuzzi, B; Mangoni, A
Abstract : Progressive Parkinsonism, dystonia and apraxia of eye opening were seen after cyanide poisoning. CT scan and MRI showed lesions in the basal ganglia, cerebellum and cerebral cortex consistent with reported pathological findings.